TRANSPARENCY AND EFFECTIVENESS IN MANAGING THE DIRECT CASH ASSISTANCE FOR VILLAGE FUNDS (BLTDD) IN THE VILLAGE OF BUNGINGKELA, SUBDISTRICT OF BUNGKU SELATAN, MOROWALI REGENCY - Burhanuddin; Nita Hasnita; Bakhtiar Abbas (BAKI (Berkala Akuntansi dan Keuangan Indonesia), 2023)
This study aims to investigate and analyze the transparency and effectiveness of the Direct Cash Assistance for Village Funds (BLTDD). The variables in this research consist of transparency and effectiveness. Data collection techniques in this study involve interviews and documentation. The informants in this research include the village head, village secretary, village treasurer, village consultative board (BPD) chairperson, and BLTDD recipients. The data analysis used in this study is a qualitative descriptive analysis. The results of this research indicate that transparency in the management of BLTDD in Bungingkela Village, Bungku Selatan Subdistrict, and Morowali Regency has not fully adhered to transparency principles. This is evidenced by the indicators of document availability and accessibility, as the Bungingkela Village government has not disseminated the list of potential BLTDD recipients. The effectiveness of BLTDD management in Bungingkela Village, Bungku Selatan Subdistrict, and Morowali Regency, assessed based on program comprehension, targeting accuracy, timeliness, goal achievement, and tangible changes, can be concluded to have been effectively implemented.